Valorization of queen scallop shells in the preparation of metakaolin-based geopolymer mortars. (1st August 2022) - Hasnaoui, Abdelaziz; Bourguiba, Amel; Sebaibi, Nassim; Boutouil, Mohamed
Abstract: This paper aims to assess the effect of the seashell waste (SW) incorporation on the performance of MK-based geopolymer mortar. The SW powder was introduced as partial replacement of MK with a substitution rate of 0, 10, 20 and 30%. Its effect on setting time, water porosity, mechanical strengths and both drying and autogenous shrinkage was investigated. A special attention was also devoted to the evaluation of the efflorescence stability. The obtained results show that partial replacement of MK by SW powder leads to limit considerably the water demand of the binder resulting in mortars with higher mechanical strengths and lower porosity and shrinkage. In addition, SW powder allows to accelerate the setting time of geopolymer mortars. The autogenous shrinkage was found to increase with increasing SW percentage. However, the total shrinkage was dominated by the drying shrinkage that represents around 85% of the total strain at 90 days regardless the SW replacement rate. In terms of efflorescence stability, the lowest efflorescence formation was attributed to the geopolymer mixture formulated with 30% of SW powder. Highlights: MK can be safely replaced by SW powder with a substitution rate up to 30% by weight. Using SW for the formulation of geopolymer mortar leads to reduce considerably the water demand of the mixture. The shrinkage of MK-based geopolymers can be limited via the incorporation of SW powder. The mechanical and the physical performances of geopolymer mortars are enhanced with the use of SW.